2023
DOI: 10.3390/su15064751
|View full text |Cite
|
Sign up to set email alerts
|

Damping of Frequency and Power System Oscillations with DFIG Wind Turbine and DE Optimization

Abstract: Wind power is one of the most promising renewable energy resources and could become a solution to contribute to the present energy and global warming crisis of the world. The commonly used doubly fed induction generator (DFIG) wind turbines have a general trend of increasing oscillation damping. Unless properly controlled, the high penetration of wind energy will increase the oscillation and affect the control and dynamic interaction of the interconnected generators. This paper discusses power oscillation damp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…The findings from the study showed that the offshore sites have four times greater wind power potential than the coastal sites. Assessing and knowing wind potential has not only have the advantage of application in generation electric energy, in [37] the application of wind in appropriate type of double fed induction generator (DFIG) type wind turbine is investigated to control frequency and power system oscillation of a system in the grid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings from the study showed that the offshore sites have four times greater wind power potential than the coastal sites. Assessing and knowing wind potential has not only have the advantage of application in generation electric energy, in [37] the application of wind in appropriate type of double fed induction generator (DFIG) type wind turbine is investigated to control frequency and power system oscillation of a system in the grid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors of [24] optimized the parameters of a VISMA for the application of a small microgrid, which is analyzed using a differential equation to minimize the increased grid stability problems caused by RESs in the last two decades. The wide control application of VISMAs in grid control of a more renewable-energy-integrated power system, including a photovoltaic-diesel microgrid with energy storage, are briefly discussed in [25][26][27]. In using a VISMA to improve frequency in the penetration of high RESs in the grid, it is advisable to use appropriate optimization techniques in order to properly select the virtual inertia constant of the VISMAs and the best control parameters for VISMAs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The process begins with a large field of mirrors, called heliostats, which track the sun and reflect its rays onto a receiver located at the top of a central tower. The receiver absorbs the heat from the concentrated sunlight, which is then used to heat a fluid, usually a synthetic oil, that flows through the receiver [34]. The heated fluid is then sent to a heat exchanger where it heats water to produce steam.…”
Section: Two-area Interconnected Power System With Solar Thermal Powe...mentioning
confidence: 99%